GEOPHYSICAL SURVEY AT THE OMALOS PLATEAU, CHANIA, CRETE - Βαφείδης, Α.; Μανούτσογλου, Μ.; Hamdan, H.; Ανδρονικίδης, Ν.; Κουκαδάκη, Μ.; Κρητικάκης, Γ.; Οικονόμου, Ν.; Σπανουδάκης, Ν. (Bulletin of the Geological Society of Greece, 2004)
This paper discusses the preliminary results of a geophysical survey that was carried out at the Omalos plateau in Chania, Crete. The geophysical survey included measurements of electrical tomography, electrical mapping, seismic refraction, georadar, VLF and gravity. The aim of this survey is to compare the results from different geophysical methods used in imaging dolines and karstic features. The processing of the measurements indicates three geoelectrical layers. The first layer of extremely high electrical resistivity is attributed to alluvial - dilluvial deposits. The second layer of very low electrical resistivity reflects mainly the presence of marls. Finally, the third geoelectrical layer outlines the carbonate bedrock, whose relief appears highly irregular. The comparison of all geophysical methods leads to the same results, concerning the detection of dolines and karstic anomalies at the Omalos plateau.